2010
DOI: 10.1124/jpet.109.165001
|View full text |Cite
|
Sign up to set email alerts
|

PRX-08066, a Novel 5-Hydroxytryptamine Receptor 2B Antagonist, Reduces Monocrotaline-Induced Pulmonary Arterial Hypertension and Right Ventricular Hypertrophy in Rats

Abstract: Pulmonary arterial hypertension (PAH) is a life-threatening disease that results in right ventricular failure. 5- pyrimidin-4-ylamino)piperidin-1-yl)methyl)-2-fluorobenzonitrile monofumarate (PRX-08066) is a selective 5-hydroxytryptamine receptor 2B (5-HT2BR) antagonist that causes selective vasodilation of pulmonary arteries. In the current study, the effects of PRX-08066 were assessed by using the monocrotaline (MCT)-induced PAH rat model. Male rats received 40 mg/kg MCT or phosphate-buffered saline and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 34 publications
3
26
0
1
Order By: Relevance
“…Briefly, absence of vascular remodelling during chronic hypoxia has been demonstrated in a 5-HTR 2B -/-mouse model and by pharmacological inhibition with the 5-HTR 2B antagonists RS127445 [43] and PRX-08066 [44] in animal models of chronic hypoxia or MCT-induced PH, respectively [18,44,45]. A possible clinical relevance of these findings is supported by two lines of evidence.…”
Section: Discussionsupporting
confidence: 51%
“…Briefly, absence of vascular remodelling during chronic hypoxia has been demonstrated in a 5-HTR 2B -/-mouse model and by pharmacological inhibition with the 5-HTR 2B antagonists RS127445 [43] and PRX-08066 [44] in animal models of chronic hypoxia or MCT-induced PH, respectively [18,44,45]. A possible clinical relevance of these findings is supported by two lines of evidence.…”
Section: Discussionsupporting
confidence: 51%
“…16 By using the monocrotaline (MCT)-induced pulmonary hypertension rat model, recent studies confirmed that other 5-HT 2B antagonists (terguride, PRX-08066, or C-122) significantly reduced pulmonary pressure, arterial wall thickening, and lumen occlusion but maintained cardiac function. [17][18][19] Independently, 5-HT was shown to stimulate human BM stromal cells and synergize with other pleiotropic growth factors that promote hematopoietic stem and progenitor cells. 20 The 5-HT action on hematopoiesis or BM microenvironment at pathophysiologic conditions warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…16 By using the monocrotaline (MCT)-induced pulmonary hypertension rat model, recent studies confirmed that other 5-HT 2B antagonists (terguride, PRX-08066, or C-122) significantly reduced pulmonary pressure, arterial wall thickening, and lumen occlusion but maintained cardiac function. [17][18][19] Independently, Submitted June 2, 2011; accepted December 15, 2011. Prepublished online as Blood First Edition paper, December 20, 2011; DOI 10.1182 DOI 10.…”
Section: Introductionmentioning
confidence: 99%
“…19 A pathophysiological role of 5-HT2B receptor (5-HT2BR) was suggested by the increased binding to 5-HT2BR in lung vascular bed of the hypoxia-induced PAH mouse model and corroborated by the results that genetic or pharmacological inactivation of 5-HT2BR prevented the development of PAH in mice. [20][21][22][23][24][25][26] 5-HT2BR is currently under active investigation as a therapeutic target for PAH. However, there is currently no evidence of 5-HT2BR-mediated constriction of pulmonary arteries in PAH.…”
mentioning
confidence: 99%